2019
DOI: 10.1002/hed.25336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of American Joint Committee on Cancer Eighth Edition clinical stage and smoking history on oncologic outcomes in human papillomavirus‐associated oropharyngeal squamous cell carcinoma

Abstract: Background The purpose of this study was to evaluate the AJCC eighth edition clinical staging system for human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma and to further understand how clinical stage and smoking history affect oncologic outcomes. The purpose of this study was to present the understanding of how clinical stage and smoking history affect oncologic outcomes in human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma (SCC) is critical for selecting pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…There have been many additional studies over the past decade analyzing the relationship between smoking and outcomes for HPV‐positive patients with OPSCC . To the best of our knowledge, the largest study to date included 1875 patients from Canada and Denmark, all of whom were treated nonsurgically.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been many additional studies over the past decade analyzing the relationship between smoking and outcomes for HPV‐positive patients with OPSCC . To the best of our knowledge, the largest study to date included 1875 patients from Canada and Denmark, all of whom were treated nonsurgically.…”
Section: Discussionmentioning
confidence: 99%
“…The combined analysis of both trials demonstrated that the low‐risk group had more favorable outcomes than the intermediate‐risk group (5‐year OS rate: 87.9% vs 66.4% [ P < .001]; and 5‐year progression‐free survival rate: 76.4% vs 53.6% [ P < .001]). However, the data were not unanimous because another large recent study (531 patients) found smoking to significantly impact OS but not locoregional failure (hazard ratio, 1.21; P = .95) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations